Attitude and factors affecting compliance to diabetes mellitus management among clinic attendees at Jericho Specialist Hospital, Ibadan - Olonisakin, Bolatito T.; Oluwamotemi, Christiana A.; Majolagbe, Nihinlola T.; Ojo, Philip A. (International Journal Of Community Medicine And Public Health, 2022)
Background: The need to understand factors influencing non-compliance with the treatment of Diabetes Mellitus (DM) will go a long way in addressing the issue in Nigeria. However, this study was aimed at assessing the attitude of diabetic patients and factors affecting their level of compliance to the management of DM among clinic attendees at Jericho Specialist Hospital, Ibadan, Nigeria. Methods: This study employed a descriptive cross-sectional study using a two-stage sampling technique. A pre-tested semi-structured questionnaire was used to obtain information on two hundred and twenty respondents. The attitude was scored on a 5-point scale where <3 and >3 were categorized as negative and positive attitudes respectively. Data were analyzed with SPSS version 21 using descriptive statistics. Results: Mean age of respondents was 49.7±10.3 years and 27.8% were male. Some (32.1%) of the respondents had a negative attitude towards the management of DM. Many 66.5%) disagreed to not bother about the outcome of their disease because they know they will get over it, 100.0% disagreed that the impact of diabetes on their lifestyle is negligible, and 65.6% agreed that they did not like people to know about their status. Amidst all the factors influencing compliance to the management of diabetes among patients with DM, drugs ranked highest with 98.1% followed by frustration due to long treatment and being tempted by inappropriate foods and drinks accounting for 83.5% and 81.1% respectively. Conclusions: There was generally a good attitude on diabetes management. However, there is a need for special programs to encourage compliance by the government.